EventMingle Management System - Waghmare, Madhavi; Ekbote, Archana; Patil, Anagha; Shirsath, Vaishali (Indian Journal of Computer Science, 2023)
The emergence of event-focused social networks has led to a significant increase in online group memberships and event invitations for millions of people. Unlike traditional social platforms, event networks require physical attendance at gatherings or events as a crucial aspect of user engagement. However, managing event announcements, dates, times, and attendee information can be cumbersome, highlighting the necessity for an efficient event management system that simplifies event discovery and attendance while fostering social interactions among users. Such a system can substantially enhance the event experience for attendees while facilitating streamlined event planning for organizers. EventMingle, a web platform, addresses this need by providing a unique approach to connecting people in diverse locations to enrich their lives. Unlike conventional social networks, EventMingle revolves around arranging offline, in-person meetings rather than merely discussing shared interests online. These gatherings often take place in public venues such as cafes, parks, and occasionally private residences. By offering a platform for users to connect and engage in shared activities, EventMingle creates opportunities to forge new friendships, actively participate in the local community, and pursue passions more actively. Organizers utilize the website to create events, enabling individuals with common interests to connect and share their enthusiasm for specific topics. EventMingle serves as a user-friendly tool for discovering and attending events in one’s local area. Given the abundance of events occurring daily, keeping track of everything, particularly for newcomers or those seeking specific types of events can be challenging. EventMingle simplifies this process by facilitating event discovery based on users’ interests and providing comprehensive details such as dates, times, and locations. The platform’s Meet-In feature allows users to find like-minded individuals, leading to the formation of close-knit communities centered around shared passions. This aspect of EventMingle is especially valuable for combating feelings of isolation and disconnection among users. Furthermore, EventMingle offers a valuable platform for personal growth and development. By connecting users with others who share similar interests. Meetup groups encourage mutual motivation and support, leading to personal growth opportunities. This feature proves particularly beneficial for individuals seeking motivation or fresh opportunities for self-improvement and advancement.